Child protection case management system - Chiweshe, Garnet S. (Midlands State University, 2018)
The purpose of this research is to come up with a system that will assist the Ministry of Public Service, Labour and Social Welfare (MPSLSW) to develop efficiencies in delivering child welfare, preventive protection, and response to violence, abuse and exploitation against children. It provides a platform for ensuring systematic handling of child protection cases amongst multiple stakeholders in Zimbabwe. The research was carried out so as to understand the problems that are being encountered when using the current system. The managers were failing to effectively supervise district level staffs who are supposed to follow through all cases, resulting in some cases not reaching their conclusion. Such a scenario was curtailing a wellintended purpose of protecting children and responding to protection violations. Inorder to address the challenges in the current system, the researcher sought to come up with a system that digitize case management data, captures referral information, produces alerts and reports and store data and information with easy retrieval of same and production of statistical reports.The researcher gathered data on how the system should like by using different research techniques which include observations, questionnaires as well as interviews. This helped the researcher come up with solutions to the problems identified. The researcher identified a gap necessitating development of a computerised system solve the problems being faced by the ministry. The system is now able to manage all information and data requirements of Case Management with features if report production, alert messages email notifications and easy case number linked information retrieval.The system developed in response was done using Microsoft Visual Studio 2012 which is from Microsoft, for the development of both console and graphic user interface (GUI) programs with windows forms applications. It is compatible to a wide range of programming languages, which allow the code editor and debugger to support (to varying degrees) nearly any programming languages, provided a language specific service exists. The developer used C# for coding the system since ease-to-development; the rich class library makes many functions easy to implemented and also good support for distributed system. As for the databases the developers used Microsoft SQL server 2008 R2 database a relational database management system from Microsoft.